Towards an effective supervision model for total quality education in some selected secondary schools in the Northern Province - Mlangeni, Simeon (My University, 2001)
Refer to document
Thesis (Ph. D. (Education)) -- University of the Limpopo, 2001
Keywords: Total quality education; Educator's supervision; Total quality management in education -- South Africa -- Limpopo; Education, Secondary -- South Africa -- Limpopo; School supervision, Secondary; School management and organization -- South Africa -- Limpopo; Educational leadership -- South Africa -- Limpopo